THE IMPLEMENTATION AND IMPLICATIONS OF THE ELECTRONIC AND INFORMATION TRANSACTIONS LAW AGAINST CYBER BULLYING BY SUBSQUENT OF THE CONSTITUTIONAL COURT DECISION RELATED TO THE FREEDOM OF SPEECH - Gumbira, Seno Wibowo; .Daryono, Daryono; Nurhayati, Ratna (Yustisia, 2017)
This article aimed to observe the criminal provisions both in the Formulation of the EIT ACT 2008 along with the verdict of the judicial review of the Constitutional Court Number 50/PUU-VI/2008 as well as the EIT ACT  2016 especially in strictly contained in article 27 along with the norm of the criminal sanctions contained in Article 45 can still be said to be a ”Rubber Articles”, so it requires linguist and religious leaders in order to get a description or explanation of a remark or action in conflict with religious values and modesty as well as decency in public life. The Guarantee Of Freedom Of Speech. Then when viewed from the highest norm of the 1945 Constitution to the level of the law that is Article "Number 9 of 1998 and Article Number 39 of 1999 there is a harmony of norms and limits of freedom of speech that is the norms and values of religion, morality, public order, public interest and the integrity of the State, the concept of punishment against the actions of cyberbullying in social media in the future require an integral approach and the concept approach is criminal on parole and penal mediation with the terms limitedly and imperative.